Detailed study of nonlinear cooling with two-terminal configurations of topological edge states - Hajiloo, Fatemeh (2020)
We study the nonlinear thermoelectric cooling performance of a quantum spin Hall system. The setup consists of a nanomagnet contacting a Kramers pair of helical edge states, resulting in a transmission probability with a rich structure containing peaks, well-type, and step-type features. We present a detailed analysis of the impact of all these features on the cooling performance, based to a large extent on analytical results. We analyze the cooling power as well as the coefficient of performance of the device. Since the basic features we study may be present in the transmission function of other mesoscopic conductors, our conclusions provide useful insights to analyze the nonlinear thermoelectric behavior of a wide class of quantum devices. The combination of all these properties defines the response of the quantum spin Hall setup, for which we provide some realistic estimates for the conditions limiting and optimizing its operation as a cooling device.